2019
DOI: 10.1111/cpr.12605
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering role of FGFR signalling pathway in pancreatic cancer

Abstract: Recently, fibroblast growth factors are identified to play a vital role in the development and progression of human pancreatic cancer. FGF pathway is critical involved in numerous cellular processes through regulation of its downstream targets, including proliferation, apoptosis, migration, invasion, angiogenesis and metastasis. In this review article, we describe recent advances of FGFR signalling pathway in pancreatic carcinogenesis and progression. Moreover, we highlight the available chemical inhibitors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 144 publications
0
36
0
Order By: Relevance
“…FGFR genes are involved in multiple biological processes, including cell transformation, angiogenesis, apoptosis, embryonic development, and tissue repair. Mutations and amplification of FGFR gene members have been shown to serve as therapeutic targets in a wide range of human malignancies, such as gastric, lung, and bladder cancers 18,19. Previous studies have demonstrated that overexpression of FGFR fusion proteins promotes tumor cell proliferation and migration 20.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR genes are involved in multiple biological processes, including cell transformation, angiogenesis, apoptosis, embryonic development, and tissue repair. Mutations and amplification of FGFR gene members have been shown to serve as therapeutic targets in a wide range of human malignancies, such as gastric, lung, and bladder cancers 18,19. Previous studies have demonstrated that overexpression of FGFR fusion proteins promotes tumor cell proliferation and migration 20.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, smoking, alcohol abuse, and a high fat and protein diet increase the risk of developing PDAC, underlining the crucial role of inflammation in pancreatic carcinogenesis which is characterized by desmoplasia-driven activation and differentiation of pancreatic stellate cells into pancreatic αSMA+/vimentin+ myofibroblasts [11][12][13]. Beside the systemic inflammatory response (SIR), emerging evidence determined that inflammation-associated vital genes, signaling pathways, and growth factors such as PI3K (phosphatidylinositol), Ras-MAPK (mitogen-activated protein kinase), STAT (signal and activator of transcription), Wnt, EGF (epidermal growth factor), and FGF (fibroblast growth factor) are involved in the carcinogenesis and progression of PDAC [14][15][16][17][18][19][20][21]. FGFs are peptide-like molecules which bind to their specific receptors (FGFR) on cell membranes to govern cell growth.…”
Section: Original Articlementioning
confidence: 99%
“…In mammals, 22 different FGFs are known today. Beside the biggest FGF subfamily, the canonical FGFs, one endocrine and one intracellular FGF subfamily exists and all FGFs mediate their cellular response via binding and activation of one of four FGFRs [14,21]. A broad range of FGFs have been investigated in vitro and in vivo for their role and influence on PDAC, including the treatment response of pancreatic cancer cells to chemotherapy and the use of anti-FGF therapy, so called "ligand-traps" [14,[22][23][24][25][26][27][28][29].…”
Section: Original Articlementioning
confidence: 99%
“…However, this novel regulatory switch does not target the CDH1 promoter. The external cues that turn this switch on include fibroblast growth factor (FGF)‐2 that is abundantly present in the tumor microenvironment 37,38 . Therefore, this regulatory switch could contribute to the phenotypic plasticity of cancer cells during malignant progression.…”
Section: Introductionmentioning
confidence: 99%